Engineering of Primary Pancreatic Islet Cell Spheroids for Three-dimensional Culture or Transplantation: A Methodological Comparative Study. (31st July 2020) - Wassmer, Charles-Henri; Bellofatto, Kevin; Perez, Lisa; Lavallard, Vanessa; Cottet-Dumoulin, David; Ljubicic, Sanda; Parnaud, Géraldine; Bosco, Domenico; Berishvili, Ekaterine; Lebreton, Fanny
Three-dimensional (3D) cell culture by engineering spheroids has gained increasing attention in recent years because of the potential advantages of such systems over conventional two-dimensional (2D) tissue culture. Benefits include the ability of 3D to provide a more physiologically relevant environment, for the generation of uniform, size-controlled spheroids with organ-like microarchitecture and morphology. In recent years, different techniques have been described for the generation of cellular spheroids. Here, we have compared the efficiency of four different methods of islet cell aggregation. Rat pancreatic islets were dissociated into single cells before reaggregation. Spheroids were generated either by (i) self-aggregation in nonadherent petri dishes, (ii) in 3D hanging drop culture, (iii) in agarose microwell plates or (iv) using the Sphericalplate 5D™. Generated spheroids consisted of 250 cells, except for the self-aggregation method, where the number of cells per spheroid cannot be controlled. Cell function and morphology were assessed by glucose stimulated insulin secretion (GSIS) test and histology, respectively. The quantity of material, labor intensity, and time necessary for spheroid production were compared between the different techniques. Results were also compared with native islets. Native islets and self-aggregated spheroids showed an important heterogeneity in terms of size and shape and were larger than spheroids generated with the other methods. Spheroids generated in hanging drops, in the Sphericalplate 5D™, and in agarose microwell plates were homogeneous, with well-defined round shape and a mean diameter of 90 µm. GSIS results showed improved insulin secretion in response to glucose in comparison with native islets and self-aggregated spheroids. Spheroids can be generated using different techniques and each of them present advantages and inconveniences. For islet cell aggregation, we recommend, based on our results, to use the hanging drop technique, the agarose microwell plates, or the Sphericalplate 5D™ depending on the experiments, the latter being the only option available for large-scale spheroids production.